HaveAniesDay Media to Improve Student Motivation and Learning Outcomes on Kingdom History Material - Permatasari, Adelia Putri; Tyas, Dewi Nilam (LPPM Undiksha, 2025)
The lack of interesting learning media on the material of the History of Kingdoms in Indonesia causes low motivation and learning outcomes for fourth-grade elementary school students. Based on this, this study aims to develop and test the feasibility and effectiveness of HaveAniesDay website-based media on the material of the history of kingdoms from Indonesia. This study uses a quantitative and qualitative research method using the Research and Development (RSD) type. The population of the study was 26 fourth-grade students. Data collection techniques include tests, questionnaires, observations, interviews, and documentation. Data collection instruments are in the form of questionnaires and test questions. The data obtained were analyzed using descriptive and inferential statistics through normality tests and paired sample T-tests in the form of Normalized Gain scores. Student learning outcomes through the T-test showed that there were differences in student learning outcomes after implementing HaveAniesDay website-based media on the material of the history of kingdoms in Indonesia. It was concluded that the HaveAniesDay website-based learning media that had been developed was very feasible and effective for use in increasing motivation and learning outcomes in social science learning on the material of the history of kingdoms in Indonesia. The implications of this study indicate that the use of innovative digital-based learning media can be an effective solution in overcoming low student interest and learning outcomes in history subjects. This media is not only able to present material interestingly and interactively but also encourages active student involvement in the learning process.